Informator Akademicki . serwis informacyjny Działu Informacji Komitetu Strajkowego, no. 15, 1981 - Biuro Informacji Studenckiej NZS PL, [ed. Sławomir Adrian et al.], [graphic design Marek Sykała] (NZS PL, 1981)
Creation and circulation: For internal use